2010
DOI: 10.3390/sym2041745
|View full text |Cite
|
Sign up to set email alerts
|

Polyanionic Hexagons: X6n– (X = Si, Ge)

Abstract: Abstract:The paper reviews the polyanionic hexagons of silicon and germanium, focusing on aromaticity. The chair-like structures of hexasila-and hexagermabenzene are similar to a nonaromatic cyclohexane (CH 2 ) 6 and dissimilar to aromatic D 6h -symmetric benzene (CH) 6 , although silicon and germanium are in the same group of the periodic table as carbon. Recently, six-membered silicon and germanium rings with extra electrons instead of conventional substituents, such as alkyl, aryl, etc., were calculated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Similar to La 2 Zn 5 Sn, the 4s and 4p bands of Zn are highly dispersive due to the remarkably wide range of Zn–Zn distances. On the other hand, there is no significant overlap between the 5s and 5p bands of Sn, and this confirms the lack of s–p hybridization. , The sharp spike around −9 eV in the DOS for La 7 Zn 21 Pb 2 (see Supporting Information) corresponds to the 6s 2 lone pair of Pb, and is another testament to this conjecture.…”
Section: Resultsmentioning
confidence: 65%
“…Similar to La 2 Zn 5 Sn, the 4s and 4p bands of Zn are highly dispersive due to the remarkably wide range of Zn–Zn distances. On the other hand, there is no significant overlap between the 5s and 5p bands of Sn, and this confirms the lack of s–p hybridization. , The sharp spike around −9 eV in the DOS for La 7 Zn 21 Pb 2 (see Supporting Information) corresponds to the 6s 2 lone pair of Pb, and is another testament to this conjecture.…”
Section: Resultsmentioning
confidence: 65%
“…We previously discovered a similar flat silicon hexagon with double aromaticity, i.e., the dianion of the Si 6 cluster (Fig. 1d) 25, 26 . This finding encouraged us to design the present flat silicene building blocks using electron-donating substituents.…”
Section: Introductionmentioning
confidence: 77%
“…It was theoretically predicted that the Si 6 monocyclic backbone retains planar geometry when all H atoms were substituted by Li atoms . Si 6 n − ( n= 2, 4, and 6) and (SiBeH) 6 are the other theoretically known compounds possessing planar Si 6 monocyclic backbone . Exploration of the PES of Si 6 Li 6 showed that the Si 6 Li 6 monocyclic structure was not the global minimum on the PES .…”
Section: Figurementioning
confidence: 99%
“…[29,30] Si 6 nÀ (n = 2, 4, and 6) and (SiBeH) 6 are the other theoretically known compounds possessing planar Si 6 monocyclic backbone. [31][32][33] Exploration of the PES of Si 6 Li 6 showedt hat the Si 6 Li 6 monocyclic structure was not the global minimum on the PES. [34] It would therefore be an interesting subject to evaluate kinetic stability of the Si 6 Li 6 monocyclic structure.In this study,w eh ave designed ak inetically stable hexasilabenened erivative with ap lanar,m onocyclic Si 6 backbone.…”
mentioning
confidence: 99%